OPTIMIZATION RESEARCH OF PREVENTIVE MAINTENANCE STRATEGY ON THE CATENARY SYSTEM BASED ON RELIABILITY CONSTRAINTS - LIU Huan; LIU ZhiGang; JIANG Jing (Jixie qiangdu)
Optimization research on reliability of the catenary system and preventive maintenance strategy is the key to ensure the safe operation of the electrical railway. The choice of preventive maintenance strategy is more conducive to develop maintenance program of catenary system. Analyzing the catenary system based on fault tree analysis model and using different parameters’ Weibull distribution to describe the device failure probability of the various parts of the catenary system. The optimization function of preventive maintenance strategy on the catenary system based on reliability constraints is deduced.According to three years’ measured fault data of Changsha section,the parameters of Weibull distribution which describe the various parts of the catenary system is fitted,the maintenance costs of the catenary system in Changsha section were calculated according to the model of optimization on preventive maintenance strategy. Conclusions showed that: appropriately increasing maintenance times can reduce maintenance costs; high reliability requires will increase maintenance times and repair costs significantly. The maintenance strategy optimization model and the calculated results provide a useful reference for the Maintenance of the catenary system.